British Women Surgeons and their Patients, 1860-1918 - Brock, Claire (Social Sciences, 2017)
Drawing upon a rich archive, Brock explores the cultural, social and self-representation of the woman surgeon in Britain from 1860 to the end of the Great War. This book is essential reading for those interested in medical history, providing wide-ranging new perspectives on the history of women, patient narratives and the history of surgery. This title is also available as Open Access.